Turbulent heat and momentum fluxes in the upper ocean under Arctic sea ice. Issue 2 (25th February 2017) - Peterson, Algot K.; Fer, Ilker; McPhee, Miles G.; Randelhoff, Achim
Abstract: We report observations of heat and momentum fluxes measured in the ice‐ocean boundary layer from four drift stations between January and June 2015, covering from the typical Arctic basin conditions in the Nansen Basin to energetic spots of interaction with the warm Atlantic Water branches near the Yermak Plateau and over the North Spitsbergen slope. A wide range of oceanic turbulent heat flux values are observed, reflecting the variations in space and time over the five month duration of the experiment. Oceanic heat flux is weakly positive in winter over the Nansen Basin during quiescent conditions, increasing by an order of magnitude during storm events. An event of local upwelling and mixing in the winter‐time Nansen basin highlights the importance of individual events. Spring‐time drift is confined to the Yermak Plateau and its slopes, where vertical mixing is enhanced. Wind events cause an approximate doubling of oceanic heat fluxes compared to calm periods. In June, melting conditions near the ice edge lead to heat fluxes of O(100 W m −2 ). The combination of wind forcing with shallow Atlantic Water layer and proximity to open waters leads to maximum heat fluxes reaching 367 W m −2, concurrent with rapid melting. Observed ocean‐to‐ice heat fluxes agree well with those estimated from a bulk parameterization except when accumulated freshwater from sea ice melt in spring probably causes the bulk formula to overestimate the oceanic heat flux. Key Points: Unique winter and spring measurements of under‐ice turbulence characteristics in the Eastern Arctic Winter oceanic turbulent heat flux toward ice is O(1) W m −2 in deep Arctic Under‐ice heat fluxes are O(100) W m −2 near Atlantic Water pathways